SYSTEM DESIGN FIRMS FOR DECISION - Del Carpio Gallegos, Javier F. (1998)
In recent years there have been changes in our economy, which have had an impact on the industrial sector. Industrial companies have been forced to become more competitive to survive in a free market economy.